Associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 with molecular subtypes, PD-L1 expression, and FGFR3 mutational status in two advanced urothelial bladder cancer cohorts - Bahlinger, Veronika; Branz, Annalena; Strissel, Pamela; Strick, Reiner; Lange, Fabienne; Geppert, Carol-Immanuel; Klümper, Niklas; Hölzel, Michael; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; et al. (Histopathology, 2024)
Aims: Treatment options for advanced urothelial carcinoma (aUC) rapidly evolved: besides immunomodulative therapeutic options and inhibitors targeting Fibroblast growth factor receptor (FGFR) alterations, two new antibody-drug conjugates (ADC), sacituzumab govitecan (SG) and enfortumab vedotin (EV), have been approved. However, little is known about the associations of specific aUC properties and the surface target expression of TROP2 and NECTIN-4. Our aim was to characterize associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 protein and gene expression with morphomolecular and clinicopathological characteristics of aUC in two large independent cohorts. Methods and results: The TCGA BLCA (n = 405) and the CCC-EMN (n = 247) cohorts were retrospectively analysed. TROP2/TACSTD2 and NECTIN-4/NECTIN-4 are highly expressed at the protein and transcript level in aUC, and their expression status did not correlate with patient survival in both cohorts. NECTIN-4/NECTIN-4 expression was higher in luminal tumours and reduced in squamous aUCs. NECTIN-4 was negative in 10.6% of samples, and 18.4% of samples had low expression (H-score <15). The TROP2 negativity rate amounted to 6.5%. TACSTD2 and NECTIN-4 expression was reduced in neuroendocrine-like and/or protein-based double-negative tumours. TROP2- and NECTIN-4-negative tumours included one sarcomatoid and four neuroendocrine aUC. FGFR3 alterations and PD-L1 expression on tumour and immune cells did not associate with TROP2 or NECTIN-4 expression. Conclusions: TACSTD2/TROP2 and NECTIN-4/NECTIN-4 are widely expressed in aUC, independent of FGFR3 alterations or PD-L1 expression, thus representing a suitable target for ADC treatment in the majority of aUC. The expression loss was associated with aggressive morphomolecular aUC subtypes, i.e. neuroendocrine(-like) and sarcomatoid aUC.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Advanced urothelial carcinoma; membranous expression; NECTIN-4/NECTIN-4; TACSTD2/TROP2; treatment options